Circular RNA circ_0001946 acts as a competing endogenous RNA to inhibit glioblastoma progression by modulating miR‐671‐5p and CDR1. Issue 8 (21st January 2019) - Li, Xinxing; Diao, Hongyu
Abstract: Objectives: In many malignant tumors, circRNAs play an important role. However, the biological role and clinical significance of circRNAs remain unclear. In this study, we investigated the effects of circ_0001946 on the progression of glioblastoma (GBM) and the molecular mechanism of circ_0001946. Methods: Microarrays were applied to test the expression profiles of circRNAs and messenger RNAs (mRNAs). Coexpressed genes were identified by constructing differentially expressed circRNA–mRNA networks. The expression of circ_0001946, miR‐671‐5p, and cerebellar degeneration‐related autoantigen 1 ( CDR1 ) was detected by real‐time quantitative PCR, and the protein expression of CDR1 was determined by western blotting. A dual‐luciferase reporter assay was used to evaluate potential miR‐671‐5p target sites on circ_0001946 and CDR1 . The proliferation, apoptosis, migration, and invasion of GBM cells were assessed by a colony formation assay, flow cytometry assay, transwell migration assay, and transwell invasion assay. Xenograft mouse models were used to determine the role of circ_0001946 in vivo. Results: The expression of circ_0001946 and CDR1 was low and that of miR‐671‐5p was high in GBM cells. Circ_0001946 suppressed the expression of miR‐671‐5p, thus upregulating the expression of CDR1, the gene downstream of miR‐671‐5p. Circ_0001946 and CDR1 reduced proliferation, migration, and invasion and increased apoptosis in GBM cells, whereas miR‐671‐5p had an opposite effect. The xenograft mouse model and immunohistochemistry results indicated that circ_0001946 inhibited GBM growth as well as the expression of Ki67 in GBM cells. Conclusion: Our study confirmed that the circ_0001946/miR‐671‐5p/ CDR1 pathway modulates the development of GBM, and this pathway might be a promising target for the development of therapeutics for GBM. Abstract : The results of our study demonstrated that circ_0001946 could sponge miR‐671‐5p and restrain glioblastoma (GBM) cell malignancy. The activation of the circ_0001946/miR‐671‐5p/cerebellar degeneration‐related autoantigen 1 (CDR1) axis may be a potential therapeutic target and contribute to the treatment of human GBM.